Introduction to nonparametric detection with applications - Gibson, Jerry D. 1946-; Melsa, James L. (IEEE Press, 1996)
As a result, parametric detectors, which are excellent when model assumptions are satisfied, do not maintain the satisfactory performance necessary for detection
Literaturverz. S. 232 - 235. - 1. Aufl. im Verl. Acad. Press, New York, erschienen
Keywords: Demodulation (Electronics); Nonparametric signal detection; Statistical hypothesis testing; Statistik; Demodulation; Informationstheorie; Signalverarbeitung; Signaldetektion; Testen